Roostertree (Calotropis procera) under different amounts and periods of incorporation on yield of coriander - Paulo César Ferreira Linhares; Patricio Borges Maracajá; Maria Francisca Soares Pereira; Janilson Pinheiro de Assis; Roberto Pequeno Sousa (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
<!--[if gte mso 9]> 800x600 <![endif]--><span style="font-size: 10.0pt; line-height: 115%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The goal of this paper was to evaluate the roostertree under different amounts and periods of incorporation on yield of coriander. This paper was conducted at the experimental farm Rafael Fernandes of, Universidade Federal Rural do Semi-Árido (UFERSA), Mossoró-RN, in the period October-December 2009. Experimental design was a randomized complete block with treatments arranged in a factorial 4 x 4, with three replications, with 144 plants per plot, with the first factor consists of the amounts of roostertree (5.4, 8.8, 12.2 and 15.6 t ha-1 on a dry basis), the second by periods of soil incorporation (0, 10, 20, and 30 days before sowing - DAS). The cultivar was planted cilantro palmtrees. The characteristics evaluated were such: plant height, number of stems plant-1, yield and dry matter weight of shoots. Significant interaction between treatments was observed for the characteristic coriander yield with better agronomic performance observed in the amount of 15.6 t ha-1 roostertree applied between incorporation 30 days before sowing coriander, with an average yield of 4404 kg ha-1.<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] -->